A novel pessimistic multigranulation roughness by soft relations over dual universe - Jamalud Din (19440781) (2023)
A multigranulation rough set over two universes delivers a unique perspective on the combination of multigranulation information. This paper presents the pessimistic multignualtion rough set over dual universes based on soft binary relations. Firstly, a new pessimistic multigranualtion rough set over dual universes based on two soft binary relations has been developed, and their properties are derived. Then we extend this idea and present pessimistic multigranulation roughness over dual universes based on the finite number of soft binary relations. Finally, we present an example to illustrate our proposed multigranualtion rough set model. Other Information Published in: AIMS Mathematics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.3934/math.2023397